2013
DOI: 10.1099/mic.0.066415-0
|View full text |Cite
|
Sign up to set email alerts
|

Modelled microgravity cultivation modulates N-acylhomoserine lactone production in Rhodospirillum rubrum S1H independently of cell density

Abstract: The photosynthetic alphaproteobacterium Rhodospirillum rubrum S1H is part of the MicroEcological Life Support System Alternative (MELiSSA) project that is aiming to develop a closed life support system for oxygen, water and food production to support human life in space in forthcoming long-term space exploration missions. In the present study, R. rubrum S1H was cultured in a rotating wall vessel (RWV), simulating partial microgravity conditions on Earth. The bacterium showed a significant response to cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Our calculations showed that the cells would not be completely dispersed through the chamber by diffusion alone in 21 days, since the mean square distance traveled by a cell due to Brownian movement in this time was theoretically ∼1.3 mm 2 . Consistent with our calculations, no aggregation was observed in the BMRs subject to microgravity while they were visible in 1 × g and 0.4 × g ( Figure 6 ), although aggregation by quorum sensing has been reported in microgravity ( Mastroleo et al, 2013 ; Condori et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our calculations showed that the cells would not be completely dispersed through the chamber by diffusion alone in 21 days, since the mean square distance traveled by a cell due to Brownian movement in this time was theoretically ∼1.3 mm 2 . Consistent with our calculations, no aggregation was observed in the BMRs subject to microgravity while they were visible in 1 × g and 0.4 × g ( Figure 6 ), although aggregation by quorum sensing has been reported in microgravity ( Mastroleo et al, 2013 ; Condori et al, 2016 ).…”
Section: Discussionsupporting
confidence: 91%
“…A third explanation is that, although the different physical environment in each gravity regime could have led to different growth rates and responses, by the end of the experiment all cells had effectively reached stationary phase, resulting in similar cell numbers within each bacterial species. Other space experiments reported comparable final cell concentrations with respect to their ground controls, despite differences in early growth phases ( Klaus et al, 1997 ; Nicholson and Ricco, 2020 ), and after several days of growth in simulated microgravity compared to normal gravity control ( Mastroleo et al, 2013 ). In our experiment, the bacterial cultures were grown for 21 days (which allowed us to maximize the bioleaching of elements from the rock).…”
Section: Discussionmentioning
confidence: 86%
“…radiodurans [ 61 ]. The genes encoding tellurium resistance have been specifically upregulated in a-proteobacterium Rhodospirillum rubrum followed by space exposure at ISS in frames of MELiSSA project, as well as significant differentially expressed under the conditions of modeled microgravity [ 62 , 63 ]. The genes encoding TerB and TerE tellurium resistance proteins in D .…”
Section: Discussionmentioning
confidence: 99%
“…The authors connect it with the detected reduced growth of B. cereus after spaceflight as an adaptive strategy that enable the survival and maintenance of the energy status. Transcriptomic analysis of space exposed B. subtilis spores and Rhodospirillum rubrum exposed to modeled microgravity in frames of the Micro-Ecological Life Support System Alternative (MELiSSA) project showed the down-regulation of genes encoding lipid biosynthetic enzymes (Nicholson et al, 2012;Mastroleo et al, 2013). Multiomic analyses showed that metabolic pathways associated with fatty acid metabolism, phospholipid biosynthetic process, and cellular lipid biosynthetic processes were affected in E. coli and Enterococcus faecium strains after spaceflight (Chang et al, 2013a;Li et al, 2015).…”
Section: Lipid Metabolismmentioning
confidence: 99%